The role of internal audit in improving the performance of local government authorities: The case of Morogoro Municipal council - Masui, Denis S. (Mzumbe University, 2024)
A dissertation submitted to School of Business in the partial fulfillment of the requirement for award of the Degree of Master in Accounting and finance of Mzumbe University